SOCIALIZATION OF FAST ARABIC READING METHODS FOR SANTRI AN-NIKMAH INSTITUTE HICIRAC IN CAMBODIA - Saproni Muhammad Samin,; Zulkifli Rusby,; Tengku Muhammad Dafa Dakhilullah, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Cambodian Muslims experienced depopulation After the Civil War when the Red Army led the Government. Along the way, with the permission of Allah SWT, Muslims are now starting to develop themselves and their religion. Of the eight hundred thousand Muslims, in 2020, the millennial generation will dominate. The Cambodian Muslim community needs assistance from fellow ASEAN countries, such as Indonesia, to develop Islamic educational institutions. Even though they are a minority, they enjoy the freedom of worship, built mosques, prayer rooms and Islamic Schools, and even formed an institution specifically for Muslims called HICIRAC (Highest Council for Islamic Affairs Cambodia). The new millennial generations who dominate Cambodia's Islamic society are their hope for a glorious future and the glory of Islam; they will be a milestone in the development of Islam in Cambodia, so they need to be provided with fast learning methods and speedy learning to read the Holy Qoran. They were educated at the An-Nikmah Institute, a superior and flagship Islamic Education Institution owned by HICIRAC. The socialization of the Saminyyah method is a small effort dedicated to enriching various ways of Al-Quran and Islamic education for the Cambodian Muslim community.